2018
DOI: 10.1371/journal.pone.0195305
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilisation prior to the diagnosis of inflammatory bowel diseases and the influence of livestock exposure: A longitudinal case-control study

Abstract: An increased prevalence of the inflammatory bowel diseases, ulcerative colitis and Crohn’s disease, was found amongst residents in a livestock dense area. We hypothesised that exposure to livestock farms might be a substantial environmental factor that contributes to the development of these diseases and that in the lead up to inflammatory bowel diseases potential risk factors can be identified. This study aimed to investigate the contribution of livestock exposure to the development of these diseases and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A strong body of evidence has shown that proximity to livestock farms can be associated with adverse health effects in humans, and with respiratory outcomes in particular (Baliatsas et al, 2017;Borlée et al, 2017;Kalkowska et al, 2018;Maassen et al, 2016;Post et al, 2019;Van den Berg, 2007;Van der Star et al, 2018;Van Dijk et al, 2016). The current study has some inconclusive results.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A strong body of evidence has shown that proximity to livestock farms can be associated with adverse health effects in humans, and with respiratory outcomes in particular (Baliatsas et al, 2017;Borlée et al, 2017;Kalkowska et al, 2018;Maassen et al, 2016;Post et al, 2019;Van den Berg, 2007;Van der Star et al, 2018;Van Dijk et al, 2016). The current study has some inconclusive results.…”
Section: Discussionmentioning
confidence: 56%
“…Livestock farms are a source of various emissions, such as particulate matter, endotoxins, and ammonia. Acute infections and chronic illnesses have recently been linked to residents of livestock dense areas (Borlée et al, 2017;Kalkowska et al, 2018;Maassen et al, 2016;Post et al, 2019;Van der Star et al, 2018). Furthermore, a variety of zoonotic pathogens are associated with both livestock farms and human health conditions (Morakinyo et al, 2016;Smit et al, 2012;Uiterwijk et al, 2017;Zomer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to specifically focus on recent episodes of lower back pain, we only considered patients who did not consult the GP for the same reason in the preceding 52 weeks. The choice of lower back pain as control diagnosis is a standard procedure for studies with this design [ 23 , 24 ]; alternative diagnoses that were considered were discarded for different reasons, e.g. because of their low frequency (e.g.…”
Section: Methodsmentioning
confidence: 99%